State Attorneys General as Agents of Police Reform - Mazzone, Jason (2020)
State attorneys general can and should play an important role in remedying police violations of constitutional rights. In 1994, Congress enacted 34 U.S.C. § 12601 to authorize the U.S. attorney general to seek equitable relief against state and local police departments engaged in patterns or practices of misconduct. The Department of Justice (“DOJ”) has used this statute to reform some of the nation’s most troubled police departments. However, the DOJ has lacked the resources to pursue more than a few cases each year, and in 2017 the Trump administration announced it would no longer enforce § 12601. In response, some state attorneys general have sought to fill the regulatory gap. These attorneys general claim legal standing under the common law doctrine of parens patriae to seek equitable relief in federal court against police departments within their states for violations of constitutional rights—even without any statutory authority for their lawsuits. Allowing these cases to proceed would give state attorneys general expansive and untapped potential as agents of police reform, with significant implications for police practices and accountability. This Article provides a cautionary tale about uses of parens patriae by state attorneys general and presents an alternative. It urges that the common law doctrine of parens patriae should not allow state attorneys general to seek equitable relief in federal district court against local police departments engaged in patterns of misconduct. The Article shows that such uses of parens patriae raise numerous doctrinal and policy concerns. Nevertheless, the Article concludes that state attorneys general are uniquely situated to provide a check on abuses by local law enforcement and that they should be given the tools to do so. As an alternative to using common law parens patriae, both Congress and state legislatures should grant state attorneys general explicit statutory authority to seek equitable relief against local police departments. Empowering state attorneys general in this manner has the potential to curb seemingly intractable problems of police violations of constitutional rights